2022
DOI: 10.1002/sus2.56
|View full text |Cite
|
Sign up to set email alerts
|

High‐entropy alloy stabilized and activated Pt clusters for highly efficient electrocatalysis

Abstract: Although Pt and other noble metals are the state‐of‐the‐art catalysts for various energy conversion applications, their low reserve, high cost, and instability limit their large‐scale utilization. Herein, we report a hybrid catalysts design featuring noble metal clusters (e.g., Pt) uniformly dispersed and stabilized on high‐entropy alloy nanoparticles (HEA, e.g., FeCoNiCu), denoted as HEA@Pt, which is prepared via ultra‐fast shock synthesis (∼300 ms) for HEA alloying combined with Pt galvanic replacement for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 61 publications
0
32
0
Order By: Relevance
“…High-entropy alloying has proven to be an efficient method to improve material stability, exploiting the large configurational entropy of multielement alloys to overcome the mixing-enthalpy barrier and thus promoting thermodynamic stability of materials at finite temperature . In addition to entropy-driven thermodynamic stability, intrinsic properties such as severe lattice distortion and strong chemical short-range order enable high-entropy alloys to exhibit compelling functional properties, including thermoelectric effects, piezoelectricity, photovoltaic conversion, shape memory, etc. The investigation of high-entropy alloys initially focused on metals, and they are defined as mixtures of five or more elements.…”
mentioning
confidence: 99%
“…High-entropy alloying has proven to be an efficient method to improve material stability, exploiting the large configurational entropy of multielement alloys to overcome the mixing-enthalpy barrier and thus promoting thermodynamic stability of materials at finite temperature . In addition to entropy-driven thermodynamic stability, intrinsic properties such as severe lattice distortion and strong chemical short-range order enable high-entropy alloys to exhibit compelling functional properties, including thermoelectric effects, piezoelectricity, photovoltaic conversion, shape memory, etc. The investigation of high-entropy alloys initially focused on metals, and they are defined as mixtures of five or more elements.…”
mentioning
confidence: 99%
“…In the meantime, heterogeneous catalysts construction and morphological control are also paramount to further adjusting their catalytic performances. 108,109,[117][118][119][120] For example, Shi et al 107 reported the non-NM HEA as a substrate to disperse, stabilize, and tune NM Pt (active sites) toward significantly improved activity, stability, and low cost. In their design, the surface Pt nanoclusters are anchored on the non-noble HEA core, which ensures high dispersity, stability, and tunability of the surface active sites through high-entropy stabilization and core-shell interactions (Figure 5C).…”
Section: Heterogenous Construction and Morphology Controlmentioning
confidence: 99%
“…(C) Schematic diagram of a heterogeneous design of HEA catalysts by FeCoNiCu@Pt nanoparticle. Reproduced with permission: Copyright 2022, Wiley 107 . (D) Elemental mappings of PtPdIrRuRh‐TiO 2 , showing the combination of HEA with other nanostructures (Scale bar = 10 nm).…”
Section: Synthetic Strategies To Prepare Hea Catalystsmentioning
confidence: 99%
“…[ 240–242 ] The tunable multi‐component active sites on the surface of high‐entropy materials offer huge opportunity to regulate the adsorption energy of reaction intermediates and ultimately the electrocatalytic activity. [ 243,244 ] Recently, the strategy of designing HE materials was also introduced in the research of metal‐based graphene analogues to improve the electrocatalytic activity. [ 245–251 ] Gu et al.…”
Section: Emerging Graphene Analogues For Efficient Electrocatalysismentioning
confidence: 99%